The significance of trained immunity in cancer - Qu, Junxing; Guo, Xinya; Wang, Xinru; Meng, Huiwen; Li, Peizhi; Sun, Zhiheng (Frontiers in Immunology, 2025)
Trained immunity (TI) represented a unique state of innate immune activation, characterized primarily by persistent epigenetic modifications in immune cells. This phenomenon was first observed during pathogen infections and vaccinations, where it manifested as enhanced defensive responses in innate immune effector cells—such as those of the mononuclear phagocyte system and natural killer cells—upon re-stimulation. Cancer was a disease with complex mechanisms, marked by the loss of normal growth regulation in cells due to genetic mutations or epigenetic dysregulation, leading to abnormal proliferation and dissemination. With hundreds of subtypes, cancer could arise in virtually any human tissue or organ. The primary cause of cancer-related mortality was metastasis, which referred to the spread of cancer cells from their original site to distant organs and accounted for approximately 90% of cancer deaths worldwide. The induction of TI involved multiple immune components including myeloid cells, natural killer cells, pattern recognition receptors, and various cytokines. Notably, the enhanced response observed during secondary stimulation remained non-specific to particular pathogens. Compared to conventional therapeutic approaches, TI demonstrated superior systemic immune activation. Simple pharmacological stimuli such as β-glucan or Bacillus Calmette-Guérin (BCG) not only triggered innate immune responses but also conferred benefits to adaptive immunity, resulting in more rapid immune activation and enhanced efficacy. TI enhanced the capacity of immune cells to recognize and eliminate cancer cells, playing a critical role in countering metastasis. In this review, we summarized existing knowledge in the field, focusing on the mechanisms underlying TI induction and its significance in combating cancer.